Digital Financial Inclusion and Student Advancement: How Digital Payment Systems and Fintech Expand Access, Affordability, and Opportunity in Higher Education Across Developing Countries - Paul (Sr.), Stanley Anthony Vivion; Joseph, Justin; Paul (Jr.), Stanley Anthony Vivion; McDonald, Coretta; Solomon, Orande Kenneatior; Rambhajan, Shenelle (Stallion Journal for Multidisciplinary Associated Research Studies, 2025)
Digital financial inclusion has emerged as a critical driver of equitable access to higher education, particularly in developing countries where students face systemic barriers related to affordability, financial exclusion, and limited access to formal banking services. The rise of mobile money platforms, digital wallets, online payment systems, and fintech innovation has transformed the landscape of student financing, tuition accessibility, and enrolment continuity. This article examines how digital payment systems contribute to higher-education advancement, with specific reference to Guyana and the broader Caribbean region. Drawing upon global development literature, financial-inclusion research, and higher-education policy analysis, the findings indicate that digital finance strengthens affordability, reduces transaction bottlenecks, expands payment flexibility, facilitates micro-scholarships, and promotes inclusive enrolment growth. Policy recommendations are outlined to support national strategies and institutional reforms that integrate digital financial tools into the higher-education ecosystem.